Income convergence in the European Union: National and regional dimensions - Ana-Maria Holobiuc (European Financial and Accounting Journal, 2020)
With advancement of the European integration process, income convergence has become a debated topic that has challenged both the academic forums andthe decision-makers' community. With the first waves of the EU enlargement, it has become indisputable for the European leaders that in order to ensure economic and political stability, the European Union has to promote convergence between countries and regions. The main purpose of this paper is to study income convergence in the European Union by taking into consideration both the national and regional dimensions. In this respect, we have examined (absolute) β- and σ-convergence between 2000 and 2018, finding evidences in favour of the neoclassical growth model assumptions. The results of our study confirm the β-convergence hypothesis as the poorer countries and regions from Central and Eastern Europe experienced higher growth rates than the developed ones. In the second part of our paper, we have tried to examine the key drivers of economic growth in the European Union (conditional β-convergence). Our study suggests that variables such as gross fixed capital formation, real labour productivity and labour force participation rate had a positive impact on convergence. In contrast, the growth rates in the European Union were hampered by over-indebtedness, high rates of inflation and unemployment. These internal vulnerabilities together with external challenges threaten the stability and prosperity of the European continent. Consequently, the European Union needs more than ever to reconsider its growth model in order to ensure long-term convergence and to avoid the polarisation between its Members.
Keywords: O40; O52; O57; 650; European Union; income convergence; NUTS 2 regions; β-convergence; σ-convergence